DISASTER MITIGATION AND RESPONSE OF GOVERNMENT: COMPARATIVE STUDIES BETWEEN KELANTAN, MALAYSIA AND JIGAWA, NIGERIA - Kehinde Adekunle Aliyu (Department of Government Affairs and Administration, Universitas Muhammadiyah Yogyakarta, 2017)
The incessant occurrences of natural and human induced disasters have become a serious menace to the World most especially in the developing countries or societies. The low level of technological know-how employed to combat disasters adds to the problem. This paper looks at the implication of lack of political will using unpolished and inaccessible methods of managing risks and disasters in both rural and urban areas of the two selected places in Malaysia and Nigeria at the expense of cheap, reliable, precise method of management and remote sensing technologies. The aim of this work is to compare the political will of the government on disaster management and asserting the roles of government and social workers in assisting the victims. Mixed method research design was adopted for the work. Data collected with the secondary data and interview Schedule for the affected community people. This was administered to a group of people in both country, which comprises male and female in the Kelantan and Jigawa respectively. The researcher conducted an interview with the participants to see how they viewed the government response to disaster management. The focus of the data collection was on the roles of government regarding the mitigation of disaster in the two community in line with family welfare.The purpose of the study was to compare the responsiveness of the both countries governments and to show how both can learn from each other’s mistakes and generally learn from developed countries.